(untitled) (Fiep Bulletin - online, 2017)
The principle of inclusive education is that schools must recognize and respond to the diverse needs ofstudents by providing them quality education. The aim of this study was to analyze the scientific production published in nationaljournals and written in English on the continuing education aimed at inclusive educators. The methodology was the integrativereview. The databases consulted were SciELO, LILACS, BVS, SEER and EBSCOhost. In total were found 30 articles publishedbetween 2006 and 2016 stood out the predominance in the main theme teaching and learning, followed by the main themeconceptions of teachers about inclusion, inclusive public policies, family interactions, continuing education, early intervention,teachers’ behavior. The area of psychology contemplated as many articles as the year with the largest publication was 2016. Thesearch mode predominated qualitative items. Given the integrative review carried out, enabled by a summary on the productionof scientific knowledge about the continuing education that is referred to inclusive educators.